Poster 191: Suture Anchor-Based Quadriceps Tendon Repair Results in Improved Patient Reported Outcomes Compared to the Transosseous Tunnel Technique. Issue 7 (30th July 2022) - Trasolini, Nicholas; Walsh, Justin; Darbandi, Azad; Rice, Richard; Forsythe, Brian; Verma, Nikhil; Cole, Brian; Yanke, Adam; Dandu, Navya
Objectives: Recent biomechanical studies have compared traditional transosseus (TO) quadriceps tendon repairs to newer techniques for suture anchor (SA) repair. However, clinical studies comparing the two techniques are limited. The purpose of this study was to compare failure rates and patient reported outcomes between TO and SA quadriceps tendon repairs. Methods: Following IRB approval, patients who underwent primary repair for quadriceps tendon rupture with transosseus tunnel (TO) or suture anchor (SA) techniques between January 2009 and August 2018 were identified from a prospectively maintained institutional database and retrospectively reviewed. Patients were contacted by email or telephone interview for satisfaction (1-10 scale), current function (1-100 scale), failure (retear), and revision surgeries; International Knee Documentation Committee score (IKDC), Knee Injury and Osteoarthritis Outcomes Score (KOOS), Lysholm questionnaire outcomes were also collected. Results: Seventy patients (92.1%) were available by phone or email at a mean of 4.64±2.53 years postoperatively (transosseus sutures: 34 and suture anchor: 42). Out of these 70 patients, there were 10 failures for an overall failure rate of 14.29% (Table 1 ). Failure rates were not significantly different between treatment groups (TO: 5/34, 14.71% vs SA: 5/42, 11.90%, p=.622) (Figure 1 ). Patients in each repair group had similar satisfaction ratings (SA: 9.17±1.95 vs TO: 8.31±2.30, p=.102). The SA group reported higher subjective function (SA: 89.08±8.40 vs TO: 76.14±23.52, p=.003) and significantly greater final IKDC scores (72.30 ± 22.08 vs 56.80 ± 16.62; p=.041). Conclusions: In conclusion, there is no significant difference in failure rate between transosseus and suture anchor repairs for quadriceps tendon ruptures at a mean of 4.64±2.53 years of follow-up. Most failures occur secondary to a traumatic reinjury within the first year post-operatively. Patients who underwent suture anchor repair reported significantly greater subjective function and final IKDC, KOOS Pain, and KOOS Quality of Life scores. Figure 1. Kaplan Meler Survival curve demonstrating equivalent survival between repair groups (p=.940) Table 2. Descriptive Analysis of Surgical Failures